Paclitaxel Plus Cetuximab as Induction Chemotherapy for Patients With Locoregionally Advanced Head and Neck Squamous Cell Carcinoma Unfit for Cisplatin-Based Chemotherapy - Marín-Jiménez, Juan A.; Oliva, Marc; Peinado Martín, Paloma; Cabezas-Camarero, Santiago; Plana Serrahima, Maria; Vázquez Masedo, Gonzalo; Lozano Borbalas, Alicia; Cabrera Martín, María N.; Esteve, Anna; Iglesias Moreno, María C.; Vilajosana Altamis, Esther; Arribas Hortigüela, Lorena; et al. (Frontiers in Oncology, 2022)
Objectives: Induction chemotherapy (ICT) followed by definitive treatment is an accepted non-surgical approach for locoregionally-advanced head and neck squamous cell carcinoma (LA-HNSCC). However, ICT remains a challenge for cisplatin-unfit patients. We evaluated paclitaxel and cetuximab (P-C) as ICT in a cohort of LA-HNSCC patients unfit for cisplatin. Materials and Methods: Retrospective analysis of patients with newly diagnosed LA-HNSCC considered unfit for cisplatin-based chemotherapy (age >70 and/or ECOG2 and/or comorbidities) treated with weekly P-C followed by definitive radiotherapy and cetuximab (RT-C) between 2010 and 2017. Toxicity and objective response rate (ORR) to ICT and RT-C were collected. Median overall (OS) and progression-free (PFS) survival were estimated using Kaplan-Meier method. Cox regression analysis was performed to determine baseline predictors of OS and PFS. Results: A total of 57 patients were included. Grade 3-4 toxicity rate to ICT was 54.4%, and there was a death deemed treatment-related (G5). P-C achieved an ORR of 66.7%, including 12.3% of complete responses (CR). After P-C, 45 patients (78.9%) continued with concomitant RT-C. Twenty-six patients (45.6%) achieved a CR after definitive treatment. With a median follow-up of 21.7 months (range 1.2-94.6), median OS and PFS were 22.9 months and 10.7 months, respectively. The estimated 2-year OS and PFS rates were 48.9% and 33.7%, respectively. Disease stage had a negative impact on OS (Stage IVb vs III-IVa: HR = 2.55, [1.08 – 6.04], p=0.03), with a trend towards worse PFS (HR= 1.92 [0.91 – 4.05], p= 0.09). Primary tumor in the larynx was associated with improved PFS but not OS (HR = 0.45 [0.22 – 0.92], p=0.03, and HR=0.69 [0.32 – 1.54], p=0.37, respectively). Conclusion: P-C was a well-tolerated and active ICT regimen in this cohort of LA-HNSCC patients unfit for cisplatin-based chemotherapy. P-C might represent a valid ICT option for unfit patients and may aid patient selection for definitive treatment.